2021
DOI: 10.15420/ecr.2021.30
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Disease in Chronic Kidney Disease: Need for a Heart–Kidney Team-Based Approach

Abstract: Chronic kidney disease and coronary artery disease are co-prevalent conditions with unique epidemiological and pathophysiological features, that culminate in high rates of major adverse cardiovascular outcomes, including all-cause mortality. This review outlines a summary of the literature, and nuances pertaining to non-invasive risk assessment of this population, medical management options for coronary heart disease and coronary revascularisation. A collaborative heart–kidney team-based approach is imperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 108 publications
0
6
0
Order By: Relevance
“…CAD significantly negatively impacts the pre-, intra-and post-transplant survival of patients with chronic kidney disease (4). Myocardial revascularization is recommended, as in the general population, in patients with unstable cardiac symptoms or chronic kidney disease for whom coronary intervention provides a long-term survival benefit (5,6). Preventive coronary intervention should not be indicated solely based on the possibility of future transplantation (1).…”
Section: Discussionmentioning
confidence: 99%
“…CAD significantly negatively impacts the pre-, intra-and post-transplant survival of patients with chronic kidney disease (4). Myocardial revascularization is recommended, as in the general population, in patients with unstable cardiac symptoms or chronic kidney disease for whom coronary intervention provides a long-term survival benefit (5,6). Preventive coronary intervention should not be indicated solely based on the possibility of future transplantation (1).…”
Section: Discussionmentioning
confidence: 99%
“…The ISCHEMIA-CKD trial, which consisted of 777 CKD subjects, revealed a significantly higher incidence of stroke, death, and initiation of dialysis in subjects who received invasive strategies (coronary angiography and revascularization) [ 19 ]. Both medical and invasive treatment risks and benefits bring a dilemma in daily practices and lead into “therapeutic nihilism” in many CKD subjects [ 19 , 20 ]. The previous study showed CKD patients have more severe CAD than patients with normal kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…Medial calcification is characterized by diffuse calcification of muscular arteries in a circumferential pattern and alteration of their contractile phenotype, while intimal calcification is associated with inflammation and focal occlusion secondary to the formation of atheroma plaque [14]. A meta-analysis of 47 studies, including patients with various stages of CKD and transplanted patients, identified a common prevalence of coronary artery calcifications across CKD stages amounting to ~60%, with an associated nearly two-to fourfold increase in mortality and cardiovascular events [60,61].…”
Section: Atherosclerosis and Vascular Calcificationsmentioning
confidence: 99%
“…The progression of the calcification process in CKD is attributed to increased exposure to calcium and phosphorus due to bone metabolic disorders and the imbalance between factors that promote calcification (receptor activator of nuclear factor-κB and receptor activator of nuclear factor-κB ligand) and factors that inhibit calcification (klotho, osteoprotegerin, and fetuin A) [60,62,63]. Furthermore, CKD disrupts the metabolism of vitamin K, leading to an additional reduction in calcification inhibitors.…”
Section: Atherosclerosis and Vascular Calcificationsmentioning
confidence: 99%
See 1 more Smart Citation